The Impact of Illustrated Storybooks on Enhancing Reading Skills in Children Aged 7-8 Years - Indarini, Pipin; Rahmadani, Ni Kadek Aris (Universitas Pendidikan Ganesha, 2024)
Early childhood reading skills often present challenges, particularly during the transition from kindergarten to elementary school. At the ages of 7–8 years, children require appropriate stimulation to develop their reading skills optimally. This study aims to analyze the impact of illustrated storybook media on improving the reading abilities of children aged 7–8 years. The aspects of reading skills examined in this study include accuracy in intonation, tone, articulation, and emphasis; clarity of voice; understanding of punctuation; and fluency and reading speed. The subjects of this study were first-grade elementary school students at the initial stage of learning to read. This research employed a descriptive quantitative approach using a pre-experimental method with a One Group Pre-Test Post-Test Design. Data were collected through observation and analyzed using descriptive quantitative analysis and hypothesis testing with a Paired Sample t-test, preceded by normality testing as a prerequisite. The findings revealed that illustrated storybook media had a significant impact on improving children's reading abilities, with a significance value of 0.001 < 0.05. Children demonstrated enhanced accuracy, clarity, and fluency in reading, including better intonation, voice clarity, and understanding of punctuation. The study concludes that illustrated storybook media is effective in enhancing the reading skills of children aged 7–8 years, particularly in terms of accuracy, clarity, and reading fluency.